Validation of a SIMIND Monte Carlo modelled gamma camera for Iodine-123 and Iodine-131 imaging. Issue 6 (June 2021) - Morphis, Michaella; van Staden, Johan A.; du Raan, Hanlie; Ljungberg, Michael
Abstract: Purpose: Monte Carlo (MC) modelling techniques can assess the quantitative accuracy of both planar and SPECT Nuclear Medicine images. It is essential to validate the MC code's capabilities in modelling a specific clinical gamma camera, for radionuclides of interest, before its use as a clinical image simulator. This study aimed to determine if the SIMIND MC code accurately simulates emission images measured with a Siemens Symbia™ T16 SPECT/CT system for I-123 with a LEHR and a ME collimator and for I-131 with a HE collimator. Methods: The static and WB planar validation tests included extrinsic system energy pulse-height distributions (EPHDs), system sensitivity and system spatial resolution in air as well as a scatter medium. The SPECT validation test comprised the sensitivity from a simple geometry of a sphere in a cylindrical water-filled phantom. Results: The system EPHDs compared well, with differences between measured and simulated primary photopeak FWHM values not exceeding 4.6 keV. Measured and simulated planar system sensitivity values displayed percentage differences less than 6.9% and 6.3% for static and WB planar images, respectively. Measured and simulated planar system spatial resolution values in air showed percentage differences not exceeding 6.4% (FWHM) and 10.0% (FWTM), and 5.1% (FWHM) and 5.4% (FWTM) for static and WB planar images, respectively. For static planar system spatial resolution measured and simulated in a scatter medium, percentage differences of FWHM and FWTM values were less than 5.8% and 12.6%, respectively. The maximum percentage difference between the measured and simulated SPECT validation results was 3.6%. Conclusion: The measured and simulated validation results compared well for all isotope-collimator combinations and showed that the SIMIND MC code could be used to accurately simulate static and WB planar and SPECT projection images of the Siemens Symbia™ T16 SPECT/CT for both I-123 and I-131 with their respective collimators. Abstract : Validation, Monte Carlo simulations, SIMIND, I-123, I-131, Static planar, WB planar, SPECT